Methylphenidate amplifies long-term potentiation in rat hippocampus CA1 area involving the insertion of AMPA receptors by activation of β-adrenergic and D1/D5 receptors. (December 2015) - Rozas, C.; Carvallo, C.; Contreras, D.; Carreño, M.; Ugarte, G.; Delgado, R.; Zeise, M.L.; Morales, B.
Abstract: Methylphenidate (MPH, Ritalin©) is widely used in the treatment of Attention Deficit Hyperactivity Disorder and recently as a drug of abuse. Although the effect of MPH has been studied in brain regions such as striatum and prefrontal cortex (PFC), the hippocampus has received relatively little attention. It is known that MPH increases the TBS-dependent Long Term Potentiation (LTP) in the CA1 area. However, the cellular and molecular mechanisms involved in this process are still unknown. Using field potential recordings and western blot analysis in rat hippocampal slices of young rats, we found that acute application of MPH enhances LTP in CA3-CA1 synapses in a dose-dependent manner with an EC50 of 73.44 ± 6.32 nM. Using specific antagonists and paired-pulse facilitation protocols, we observed that the MPH-dependent increase of LTP involves not only β-adrenergic receptors activation but also post-synaptic D1/D5 dopamine receptors. The inhibition of PKA with PKI, suppressed the facilitation of LTP induced by MPH consistent with an involvement of the adenyl cyclase-cAMP-PKA dependent cascade downstream of the activation of D1/D5 receptors. In addition, samples of CA1 areas taken from slices potentiated with MPH presented an increase in the phosphorylation of the Ser845 residue of the GluA1 subunit of AMPA receptors compared to control slices. This effect was reverted by SCH23390, antagonist of D1/D5 receptors, and PKI. Moreover, we found an increase of surface-associated functional AMPA receptors. We propose that MPH increases TBS-dependent LTP in CA3-CA1 synapses through a polysynaptic mechanism involving activation of β-adrenergic and D1/D5 dopaminergic receptors and promoting the trafficking and insertion of functional AMPA receptors to the plasma membrane. Highlights: Methylphenidate (MPH) augments electrically induced LTP in the rat hippocampus (CA1). It does so via β-adrenergic and D1/D5 receptors activation. The increase of LTP by MPH involves the activation of the cAMP-PKA dependent cascade. MPH promotes AMPA receptor trafficking by phosphorylation of the S845 GluR1 subunit. MPH promotes the insertion of functional AMPA receptors in the plasma membrane.